From Embarrassment to Brand Hate: A Netnography of Negative Emotions, Detachment, and Consumer Arrogance in Foreign F&B in Aceh - Sorayanti Utami; M. Ridha Siregar; Hendra Halim (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study examines how brand embarrassment escalates into detachment and hate among Acehnese consumers toward foreign F&B brands perceived to be affiliated with Israel. Using qualitative netnography, we observed public discourse across Instagram, TikTok, X, Facebook, YouTube, Google Maps reviews, and food-delivery apps from July 2024 to August 2025. The corpus comprised 512 discourse units and eight focal incidents; 378 units explicitly invoked geopolitical ties. Event-centered coding shows primary triggers were geopolitical affiliation/solidarity (41.3%) and corporate stance/donation controversies (16.1%), followed by service humiliation (19.6%), status threat/face loss (10.3%), and pricing opacity (7.7%); halal-certification uncertainty appeared mainly as a secondary co-argument (12.2% of the geopolitical subset). Embarrassment—direct (in-store) or vicarious (online)—was typically followed by early detachment (unfollow/avoidance/switching within <48 hours) and, when coupled with moralized framing and slow/defensive corporate replies, escalated into brand hate with boycott calls (71.8% of geopolitical-triggered units). Consumer entitlement cues (16.4%) acted as an escalator, prolonging threads. Fast, empathic responses and clear statements about local franchise autonomy shortened escalation. The study contributes an episode-based process model and offers a practical playbook for risk monitoring and recovery in value-sensitive markets.